Hungary in the Sustainable Social Europe - Metzker Erika (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2021)
Abstract. In this study, the author reviews the dynamics of novel changes in the world (e.g., the coronavirus epidemic) and their social impact. It shows where Hungary has come with social developments in this period, how it has received the situation, and also draws the curve of the planned developments and their role in social sustainability. The author emphasizes that in the case of changes associated with social crisis situations, it is even more necessary to pay attention to the management of poverty, social exclusion and the strengthening of the social network. To this end, targeted use of EU funds is needed to strengthen even more effective preparedness for future situations. It presents good practices from social developments.

Резюме. У цьому дослідженні автор аналізує динаміку новітніх змін у світовому масштабі (напр. епідемія коронавіруса) та їх соціальний вплив. Показано чого досягла за цей період Угорщина у сфері соціального розвитку, як вона відреагувала на цю ситуацію, зображено криву запланованого розвитку та його роль у стійкому соціальному розвитку. Автор наголошує, що у випадку змін, пов’язаних з ситуаціями соціальної кризи необхідно звертати більше уваги на контроль бідності, соціальної ізоляції та зміцнення соціальної мережі. З цією метою необхідно цільове використання фондів ЄС для зміцнення й більш ефективної готовності до майбутніх ситуацій. Дослідження надає практичні вказівки щодо соціального розвитку.

A jelen tanulmányban a szerző a világban tapasztalható újszerű változások (pl.: a koronavírus-járvány) dinamikáját és azok társadalomra gyakorolt hatásait vizsgálja. Betekintést nyerünk, hogy Magyarország merre tart a kutatott időszakban a társadalmi fejlesztések terén, hogyan fogadta az ország a helyzetet, valamint megismerkedhetünk a tervezett fejlesztésekkel és azok társadalmi fenntarthatóságban betöltött szerepével. A szerző kiemeli, hogy a társadalmi krízishelyzetekkel járó változások esetén még inkább oda kell figyelni a szegénység, a társadalmi kirekesztettség kezelésére és a szociális háló erősítésére. Az európai uniós források célirányos felhasználására van szükség, hogy a jövőbeli helyzetekre való felkészültség még hatékonyabbá váljon. A munka bemutatja a társadalmi fejlesztések jó gyakorlatait.
Угорщина у сталій соціальній Європі
Magyarország a fenntartható szociális Európában
https://kmf.uz.ua/wp-content/uploads/2022/04/limes-2021-issue-viii_2021-12-30.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00009320
Keywords: Dynamics of change; novel challenges; opportunities inherent in change; development towards solutions; social developments in Hungary; development opportunities in the European Union; good practices for social sustainability